Effects of roasting and deodorisation on 3-monochloropropane-1, 2-diol esters, 3, 4-benzopyrene and trans fatty acids in peanut oil. Issue 3 (4th March 2022) - Gao, Pan; Zheng, Yuling; Liu, Hui; Yang, Wei; Hu, Chuanrong; He, Dongping
ABSTRACT: Hazardous substances are readily produced during roasting and deodorisation in the preparation of peanut oil. The aim of this work was to investigate the variation of 3-monochloropropane-1, 2-diol ester (3-MCPDE), 3, 4-benzopyrene (BaP) and trans fatty acid (TFA) contents in the roasting and deodorisation segments of peanut oil production process. Roasting temperatures and durations significantly affected the contaminants contents in peanut oil; they increased significantly at a roasting temperature >210°C and time >60 min. In the deodorisation segment, the BaP and TFA contents were over the standard limits at a deodorisation temperature >210°C and time >140 min. Analysis showed that 3-MCPDE was significantly correlated with the formation of C18:2T (r = 0.979) and there was a linear relationship between BaP and C18:1T (Y = 0.509 C18:1T). This information will provide guidance for the precise and appropriate processing of peanut oil.